2007
DOI: 10.1016/j.jss.2007.03.038
|View full text |Cite
|
Sign up to set email alerts
|

RB Activity Alters Checkpoint Response and Chemosensitivity in Lung Cancer Lines

Abstract: These results demonstrate that RB reconstitution into RB-deficient NSCLC lines establishes regulation of certain RB/E2F target genes and restores G1 arrest mechanisms. Furthermore, introduction of RB enhances the G1 checkpoint response to chemotherapeutics and decreases chemosensitivity. Knowledge of RB-dependent chemosensitivity may ultimately contribute to individualized therapy based on molecular characterization of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…The retinoblastoma tumor suppressor (RB) is a key regulator of cell cycle progression and is functionally inactivated in the majority of NSCLC tumors608. Hypophosphorylated RB blocks cell cycle progression, and phosphorylation of RB (to form pRB) inactivates RB, permitting progression through the cell cycle.…”
Section: 0 Cell Cyclingmentioning
confidence: 99%
See 2 more Smart Citations
“…The retinoblastoma tumor suppressor (RB) is a key regulator of cell cycle progression and is functionally inactivated in the majority of NSCLC tumors608. Hypophosphorylated RB blocks cell cycle progression, and phosphorylation of RB (to form pRB) inactivates RB, permitting progression through the cell cycle.…”
Section: 0 Cell Cyclingmentioning
confidence: 99%
“…Hypophosphorylated RB blocks cell cycle progression, and phosphorylation of RB (to form pRB) inactivates RB, permitting progression through the cell cycle. Transfection of RB into RB-deficient NSCLC cells enhanced the G1 checkpoint response to chemotherapy608. Transfection of RB into RB-deficient NSCLC608 or SCLC609 cells also significantly increased resistance608 or resulted in a trend towards increased resistance609 to cisplatin608, 609, etoposide608, 609, doxorubicin609 and 5-fluorouracil608, while dexamethasone-induced dephosphorylation of pRB in NSCLC cells was associated with antagonism of paclitaxel-induced cytotoxicity574.…”
Section: 0 Cell Cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…E2F1-induced apoptosis was previously demonstrated to correlate well with p53 stabilization in response to DNA damage, whereas in the absence of an active p53 protein, one or more E2F1 pro-apoptotic transcriptional targets, such as p73, Bim,were shown to be notably upregulated (Putzer 2007;Real et al 2006). On the other hand, p53-null cells have been denoted to be signiWcantly protected from apoptosis by Rb protein, in an E2F1-dependent manner (Angus et al 2002;Reed et al 2007). …”
Section: Fig 10mentioning
confidence: 99%
“…In our study, the highest resistance was observed for the anti-metabolite 5-FU, which is an S-phase dependent cytostatic. Its cytotoxic efficacy declined in Rb-knockdown clones by 10%–40% as compared to the nonsense control, irrespective of the Rb-knockdown extent (IC 50  = 41 µM), which could be explained by the slower growth of the modulated cell populations (data not shown) and by presumably increased levels of thymidilate synthase (TS), the cellular target of 5-FU, as described for cells without Rb [41]. A study performed on adult somatic cells revealed that following spontaneous immortalization and loss of functional p53, 5-FU failed to induce cell cycle arrest despite the presence of Rb [42].…”
Section: Resultsmentioning
confidence: 84%